General Strategies for Preparing Hybrid Polymer/Quantum Dot Nanocomposites for Color Conversion - Guan-Hong Chen; Chen-Te Lin; Po-Hsun Chen; Tyng-Woei Jang; Hsueh-Shih Chen (Nanomaterials, 2023)
Quantum dots (QDs), with their exceptional optical properties, have emerged as promising candidates to replace traditional phosphors in lighting and display technologies. This study delves into the integration strategies of QDs within glass and polymer matrices to engineer advanced quantum dot color converters (QDCCs) at the industrial scale for practical applications. To achieve enhancements in the photostability and thermal stability of QDCCs, we explore two distinct approaches: the dispersion of QDs in a hydrophilic glass matrix via a sol–gel process and the incorporation of QDs into a non-polar acrylate monomer to formulate QD/polymer nanocomposites. This research further investigates the optical behaviors of these composites, focusing on their light-scattering and propagation mechanisms, which are critical for optimizing light extraction efficiency in QDCCs. Additional optical film and light-scattering particles can improve color conversion efficiency by ~140%. These advancements present a significant step forward in the development of high-performance, energy-efficient, QD-based lighting and display systems.